2018
DOI: 10.1177/2050640618755237
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life evaluation of the safety, efficacy and therapeutic outcomes of endoscopic submucosal dissection in a Western tertiary centre

Abstract: Background: Endoscopic submucosal dissection (ESD) enables accurate pathological evaluation and low recurrence rates. Large series describing ESD outcomes in Western countries are scarce. Objective: To evaluate the real-life experience of ESD in a single Western centre. Methods: Data of all the patients submitted to ESD in our centre were prospectively recorded in a database, from the first procedure in 2011 until May 2017. Feasibility, en bloc and R0 resection rates and safety were assessed. Results: Three hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…, and concluded that duodenal ESD is useful for larger (>20 mm) lesions (21). As for the West, the contribution to the literature is relatively recent: only a handful of duodenal ERs were reported recently (22)(23)(24), yet series with comparable sizes (i.e. n=166 duodenal ERs in Pérez-Cuadrado-Robles et al's study) are being published from specialized referral centers (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, and concluded that duodenal ESD is useful for larger (>20 mm) lesions (21). As for the West, the contribution to the literature is relatively recent: only a handful of duodenal ERs were reported recently (22)(23)(24), yet series with comparable sizes (i.e. n=166 duodenal ERs in Pérez-Cuadrado-Robles et al's study) are being published from specialized referral centers (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…n=166 duodenal ERs in Pérez-Cuadrado-Robles et al's study) are being published from specialized referral centers (25,26). The main reason for this is that, similar to other sites of the gastrointestinal tract, the western experience with duodenal ESD and EMR was limited compared to the Far East (22)(23)(24)(27)(28)(29)(30)(31)(32), due to flat learning curve of these techniques and lack of training facilities for the endoscopists in the west (17,(33)(34)(35). In fact, as reported by Yamamoto et al, even in Japan where these procedures were developed and mastered, duodenal ESDs are performed in only a few institutions, due to the high risk of complications (19).…”
Section: Discussionmentioning
confidence: 99%
“…in all rectal lesions that cannot be resected in 1 fragment by snare, to always have en bloc resection in this area. This strategy is based on our large experience with ESD, very good outcomes, 2 and a high rate of malignant lesions in the rectum (nearly 25%). 3 The authors 1 reported 278 rectal lesions, with a high rate of SMIC (n ¼ 42; 15%).…”
Section: Q1mentioning
confidence: 99%
“…However, Western experience of ESD remains scarce owing to the lower incidence of esophageal SCC and the lesser capability of using ESD to treat early disease and dysplastic lesions than in Eastern countries. Santos-Antunes et al reported adequate curative resection rates in the biggest Western ESD series; nevertheless this still included only a small number of patients with esophageal tumors [4]. Thus, in Western countries accumulation of data with larger cohorts is needed regarding the feasibility of ESD for esophageal SCC.…”
mentioning
confidence: 99%